IoT Integrated Electric Car Energy Monitoring System: Case Study of IMEI TEAM UMSIDA - fudin, muchammad alif; Sulistiyowati, Indah; Falah, Agus Hayatal (Jambura Journal of Electrical and Electronics Engineering, 2024)
The increasingly rapid development of technology accompanied by the ever-increasing consumption of fossil fuels has a negative impact on environmental sustainability and provides challenges related to innovation regarding these problems. Electric fuel vehicles are one of the relevant innovations to reduce air pollution and minimize exhaust emissions from fossil fuel vehicles on global warming. IMEI TEAM UMSIDA continues to contribute to the development of vehicles powered by electric energy by participating in energy-saving vehicle competitions such as KMHE and Shell Eco Marathon. In developing electric cars, the IMEI TEAM UMSIDA experienced problems related to obtaining information on the car's energy consumption in real time or when the car was on the track. This problem prompted researchers to create a tool that is capable of monitoring car energy consumption in real time and can be accessed remotely. The experimental method is the right method for this research, because with this method the researcher carries out many experiments to ensure that the tool system works well. The parameters produced in this research are voltage, current, power and energy values in units of time. This tool is equipped with an IoT-based communication system with an internet network as a link between the user, hardware system and software system which functions to carry out remote monitoring in real time. The test results show that this tool functions well and is able to carry out voltage measurements with an error percentage of less than 0.1% and current measurements with an error percentage of less than 0.2%.